Multifrequency tympanometry findings in Newborns and Infants - Nezehat Özgül Ünlüer; Meral Didem Türkyılmaz; Bilgehan Budak; Erol Belgin (Hacettepe University, 2014)
Objectives: We aimed to evaluate the correlation between transient otoacoustic emission and multifrequency tympanometry measurements in the ages of 0-28 weeks neonates and infant group in this study. Materials and Methods: In this study, 245 right and left ears, screened by transient otoacoustic emission were evaluated in Hacettepe University Audiology and Speech Pathology Department. Tympanometric and transient otoacoustic emission measurements were applied after otoscopic examination. During analysis, SPSS 13,0 statistics programme was used. Ethics Committee approval was taken for this study. (Date of ethics committee approval:24.05.2007; LUT 07/43-18). Results: Although there were not any significant difference in tympanometric peak pressure, we just found significant difference in left ears according to static acoustic admittance who passed and who did not pass transient otoacoustic emissions in 226-678-1000 Hz probe tones. Also we found significant difference in tympanometric types in babies who passed and who did not pass transient otoacoustic emission. Conclusion: The use of 226 Hz probe tone tympanometry to detect middle ear dysfunction particulary for ages less than seven months may produce contradictory test outcomes. Our results indicated that 1000 Hz probe tone tympanometry is valid and efficient way in evaluating middle ear status in newborns and infants below the ages of 28 weeks.